PERAN SUBAK DALAM MENGURANGI ALIH FUNGSI LAHAN DI KELURAHAN PENATIH, KOTA DENPASAR - K. Raditya Krisna Dipayana; I Nyoman Harry Juliarthana (Pranatacara Bhumandala: Jurnal Riset Planologi, 2021)
Subak is a community organization that functions to regulate the distribution system of irrigation flows that irrigate each plot of rice fields. Based on data from the Denpasar City Agriculture Office, the area of ​​rice fields in 2017 reached 2,464 hectares. Then, in early 2018 it became 2,444 hectares, or shrunk by 20 hectares. Therefore the authors conducted research on; First, identify the role of subak in reducing land use change that occurs in Penatih Village with its 3 subaks included in the government program, namely sustainable subak; Second, investigate what factors can reduce land conversion in Denpasar City, especially in Penatih Village. The purpose of this study was to determine the role of subak in reducing land conversion in Penatih Village and the dominant factors that play a role in reducing the rate of land conversion. Using descriptive qualitative and quantitative methods, this study found that subak has an important role in reducing the rate of land use change. This can be seen from the mindset that Subak already knows what land is and land use change. From the technology of rice fields, it is also currently easier for Subak to manage agricultural land. Now, how can Subak apply the existing and mutually agreed upon awig - awig to reduce land conversion and plan to develop the existing potential so that the income of farmers will increase. The dominant factors that play a role in reducing land use change are the rice field technology factor from the mindset subsystem, the awig - awig factor and subak organization from the social subsystem, and the suitability of land and rice fields from the physical subsystem.